On the basic extraction properties of a phenyl trifluoromethyl sulfone-based GANEX system containing CyMe4-BTBP and TBP - Halleröd, Jenny; Wagner, Christoph; Panak, Petra (Solvent extraction and ion exchange, 2018)
A Grouped ActiNide EXtraction (GANEX) process for the extraction of actinides from used nuclear fuel for transmutation purposes has been investigated. The studied solvent consists of phenyl trifluoromethyl sulfone (FS-13), CyMe4-BTBP, and TBP, a combination that has previously shown promising results. The time to reach extraction equilibrium for the system has been found to be less than 20 min. A 2:1 complex has been found between CyMe4-BTBP and americium(III) or curium(III), whereas plutonium(IV) and CyMe4-BTBP create a 1:1 complex. The extraction of fission product is low in the system.
Im Titel die 4 ist tiefgestellt
Gesehen am 21.08.2019